The effect of group size and task involvement on temporal binding window in clap perception - Niizato, Takayuki; Nishiyama, Yuta; Zempo, Keiichi; Koike, Yuka; Arai, Koki (Frontiers in Psychology, 2024)
We collect various types of information from our environment and organise it to create a coherent representation. Several researchers have suggested that multiple signals within the temporal binding window (TBW) can be integrated into a single coherent experience, such as flashes, beeps, and the McGurk effect. However, there is no evidence that TBW distortion also occurs in group interactions. This study investigates the influence of group size (i.e., the group size effect) and the degree of task involvement in temporal perception using computer-generated clap sound experiments. Participants listened to the randomly generated clap sounds and evaluated whether they were synchronised. We established three conditions based on different levels of task involvement: low (L), middle (M), and high (H) conditions. The varying task involvements reflect how participants interact with the clap sounds, ranging from passive listening in the L condition to actively generating sounds by pressing a key in the M condition, or attempting to synchronise key pressing sounds with the sounds in the H condition. Our experiments show a robust group size effect on TBW, regardless of the different conditions. In other words, as the group size increases, participants perceive the group clap as a single event. Furthermore, we found that the uncertain cause-effect relationship condition (H condition) shows the highest TBW.Interestingly, the TBW in the rigid cause-effect relationship (M condition) is the same as that in the no involvement condition (L condition). Our results suggest that a widened TBW in collective behaviour may facilitate cohesive action, enabling individuals to adapt to the group in relatively uncertain contexts.